Assessing Leaching Requirement an Ameliorated Saline Soil in a Lysimeter Experiment - Cahyoadi Bowo; Vivi Fitriani; Marga Mandala (UNIVERSITY OF LAMPUNG, 2024)
Soil salinity problems in the coastal hinterland region of East Java diminish agricultural development and land productivity. Soil leaching is expected to reduce soil salinity. This study investigated the effectiveness of different ameliorant compositions and leaching requirements (LR) in the leaching process. The experiment involved applying ameliorants (T) and leaching (L) treatments to lysimeters filled with saline soil. The ameliorant treatments included biochar, organic matter, and gypsum. The results showed the leaching requirement capacity to reduce electrical conductivity from 5.7 dS m-1 to below 2 dS m-1. Leaching for T0 (without ameliorants) and T1 (10 Mg ha-1 of biochar) required 943 mm of water, while T2 (20 Mg ha-1 of biochar) and T3 (40 Mg ha-1 of compost) required 1052 mm. The T4 (10 Mg ha-1 of compost and 2 Mg ha-1 of gypsum) necessitated 1154 mm of leaching water. The ameliorants’ application and assortment increased the water demand for leaching. The findings indicated a consistent relationship between TDS and salinity, indicating the soil’s dominant presence of salty ions.